Spectrophotometric Determination of Cu(II) by Complex with Ethyl Cyano(2-Methyl Carboxylate Phenyl Azo Acetate) (ECA) - Mezaal, Elham Nghaimesh; Sadiq, Kawther Ahmad; Zaki, Asmaa Nihad; Rumez, Rasmia Mahmood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new simple and sensitive spectrophotometric method for the determination of trace amount of Cu(II) in the ethanol solution have been developed. The method is based on the complexation of Cu(II) with ethyl cyano(2-methyl carboxylate phenyl azo acetate) (ECA) in basic medium of sodium hydroxide givining maximum absorbance at (Î»max = 521 nm). Beer’s law is obeyed over the concentration range (5-50) (Î¼g / ml) with molar absorptivity of (3.1773 Ã— 102 L mol-1 cm-1) and correlation coefficient (0.9989). The optimum conditions for the determination of Cu(II)-complex and have been studied and applied to determine Cu(II) in synthetic water sample using simple and standard addition methods.